Multi-band circular polariser based on periodic metallic strip array. (2017) - Mangi, Farman Ali; Xiao, Shaoqiu; Mallah, Ghulam Ali; Jamro, Deedar Ali; Memon, Imran; Kakepoto, Ghulam Fatima
The multi-band circular polariser is proposed to convert linear-to-circular polarisation using 3 × 3 metallic strips array. The metallic periodic strips are printed on both sides of the dielectric substrate which enhances the axial ratio bandwidth at resonance frequencies. In this paper, the novel approach of 'fission transmission of electromagnetic waves' is utilised to obtain strong optical activity within the structure. It means that the incident linearly polarised wave is converted into two orthogonal components through the lower printed metallic strips layer of the structure. Similarly, when two transmitted orthogonal components impinge on the upper printed strips, they are converted into four orthogonal vector components at the end of structure. This projection and transmission sequence of incident and transmitted wave sustain the chain transmission of electromagnetic wave and can achieve strong circular dichroism. Moreover, the axial ratio of Txx to Txy is greater than 1 dB and the cumulative multi-band axial ratio bandwidth of 20.47% was obtained at frequency bands for the circular polarisation. This new concept and performance are theoretically investigated and verified by experimental results. Theoretical analysis and microwave experiments are presented to validate the performance of the structure which has successfully proven to operate in tandem.